Pengaruh Keberagaman Gender Dewan Direksi, Komite Audit dan Komisaris Independen Terhadap Agresivitas Pajak - Amiliya, Amiliya; Fajriana, Icha (MDP Student Conference, 2024)
The aim of this study is to find out whether the gender diversity of the board of directors, audit committee and independent commissioners can influence tax aggressiveness in property and real estate sector companies on the Indonesia Stock Exchange for the 2020-2022 period. The approach used is a quantitative approach with secondary data types. The technique used in sampling was purposive sampling technique and obtained 24 companies as samples. The data analysis method used in this research is the multiple linear regression test. The results of the test are that the gender diversity of the board of directors has a significant effect on tax aggressiveness, the audit committee does not have a significant effect on tax aggressiveness and independent commissioners have a significant effect on tax aggressiveness.